The Socio-Economic Impacts of Medupi Power Station on Lephalale - Nyembe, Thembi (My University, 2018)
The minerals-energy complex development has generated divergent interests between profit-making entities and the communities rebelling for a stake in the economic benefits of the rural town of Lephalale in Limpopo Province. The expanding minerals-energy complex in Lephalale is attractive to major domestic and global corporations. However, the Lephalale Local Municipal authority is proving to be powerless to deal with the socio-economic challenges set off by the investment. Eskom’s corporate social responsibility/investment is inadequate to deal with the socio-economically and ecologically-subjugated communities, which along with workers occasionally resort to violent protest. This case site allows exploration of a contrasting “post-positivist approach” which acknowledges the vital role of conflict and political actors in public policy and project implementation. It further explores the “positivist approach” which leads some to consider markets as the most effective means for social decisions, hence a reliance on Eskom’s corporate investments to offset damages. This qualitative research employs primary and secondary documents as well as interviews to describe the socio-economic impacts of Eskom’s Medupi Power Station on Lephalale.
Research Report Submitted in partial fulfilment of the requirements for the degree of Master of Management in Public Policy,University of the Witwatersrand, School of Governance
Keywords: Medupi Power Station; Nuclear power plants; Environmental policy--South Africa